Utilization and evaluation of Citrus natsudaidai peel waste as a source of natural food additives. (30th March 2022) - Matsuo, Yu; Akita, Kanako; Taguchi, Honoka; Fujii, Shuji; Yoshie-Stark, Yumiko; Araki, Tetsuya
Highlights: Naringin and neohesperidin were predominant flavonoids in C. natsudaidai (CN) peel. CN peel pectin had lower viscosity than commercial products. Consumer panelists accepted the CN-flavored solution with CN peel extracts. CN peel extracts can provide commercial beverages in Japan. CN peel waste can be utilized as a natural food additive in practical use. Abstract: This study aims to obtain beneficial ingredients from Citrus natsudaidai (CN) peel waste. The yields of ingredients were 26.2–31.6 mg/g dried material (DM) in pectin, 466–581 mg/g DM in insoluble dietary fiber, 5.56–7.15 g/kg fresh material (FM) in the hexane extracts obtained from CN peels, 23.8–27.0 mg/g DM in naringin, and 8.30–10.2 mg/g DM in neohesperidin. A sensory evaluation and instrumental assays using an Electronic nose and Electronic tongue were performed to evaluate aqueous solutions flavored with 0.02% hexane extracts obtained from CN peels. CN-flavored solutions had a preferred smell over commercial citrus-flavored drinks and were classified into the same group as commercial citrus juices in the Electronic nose assay. In addition, CN-flavored solutions showed sourness, bitterness, and orange-like taste, and the overall acceptance of CN-flavored solutions did not significantly differ from commercial citrus-flavored drinks. CN peel waste can be industrially utilized as a source of natural food additives.